Analisis Strategi Pengembangan Usaha Dengan Penggunaan QRIS Sebagai Metode Pembayaran Pada Rumah Makan Joglo Lumintu - H, Fendy Hariatama; Alexandro, Rinto; Rahman, Rahman; Kharisma Nugraha Putra; Mega Agustini; Alia Friskila (Edunomics Journal, 2025)
This study aims to analyze the implementation of QRIS (Quick Response Code Indonesian Standard) as a digital payment method at Joglo Lumintu Restaurant, Palangka Raya City, and examine its impact on business development strategies and operational efficiency. This research uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, participatory observation, and questionnaires to the owner, employees, and customers of the restaurant. The results showed that the use of QRIS has provided convenience and security in the transaction process, increased operational efficiency through reduced transaction time, and facilitated more transparent financial records. However, the implementation of QRIS is still hampered by the preference for cash payments among older customers, who are less familiar with digital technology. In addition, QRIS transaction recording is still done manually, indicating the need for a more comprehensive digital management system integration. QRIS implementation is proven to increase customer satisfaction, especially among the younger generation, and has the potential to support business competitiveness. This research highlights the importance of digital education to customers and improving restaurant operations as strategies for developing a more efficient and modern culinary business.